Pengaruh Penataan Tempat Duduk Berhadapan Terhadap Keterampilan Berkomunikasi Siswa SMP pada Mata Pelajaran Bahasa Indonesia - Hasanah, A. Sanaul (PINISI :Journal of Teacher Professional, 2024)
Classroom management is a determinant of classroom success. This study aims to find out more about the effect of classroom management in the form of seating arrangements facing each other on the communication skills of junior high school students in Indonesian language subjects. This research uses a class action method with two cycles. The results of this study show that the implementation of face-to-face seating arrangement as well as learning activities that support student interaction has had a positive impact on the gradual improvement of students' communication skills. Cycle II showed a significant improvement in students' communication skills, although there were still some students who needed more attention. Therefore, it is recommended to continuously implement effective learning strategies, provide additional support for students who are still experiencing difficulties, develop varied lesson plans, and involve students in the learning process to create an environment conducive to the development of students' overall communication skills.